1951
DOI: 10.1098/rspb.1951.0021
|View full text |Cite
|
Sign up to set email alerts
|

Action of nitrogen trichloride on certain proteins II. Synthesis of methionine sulphoximine and other sulphoximines

Abstract: Methionine sulphoximine (I, R ═ CH 2 CH 2 CH(NH 2 )COOH, R' ═ CH 3 ) can be synthesized by the action of hydrazoic acid on methionine sulphoxide in the presence of concentrated sul-phuric acid as a catalyst and is shown to be identical with the toxic factor isolated from nitrogen trichloride-treated proteins. S-methylcysteine sulphoximine (I, R … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
3

Year Published

1952
1952
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(7 citation statements)
references
References 9 publications
0
4
0
3
Order By: Relevance
“…[7] Die Verbindung konnte anschließend durch die Umsetzung von Stickstoffwasserstoffsäure mit Methioninsulfoxid (1) in Gegenwart konzentrierter Schwefelsäure synthetisch hergestellt werden (Schema 1). [8] Die Sulfoximingruppe war bis dahin unbekannt gewesen. Natürlich war MSO (2) kein Naturstoff, da es chemisch aus peptidgebundenem Methionin in Weizen entstanden war.…”
Section: Die Späte Entdeckung Der Sulfoximingruppeunclassified
See 2 more Smart Citations
“…[7] Die Verbindung konnte anschließend durch die Umsetzung von Stickstoffwasserstoffsäure mit Methioninsulfoxid (1) in Gegenwart konzentrierter Schwefelsäure synthetisch hergestellt werden (Schema 1). [8] Die Sulfoximingruppe war bis dahin unbekannt gewesen. Natürlich war MSO (2) kein Naturstoff, da es chemisch aus peptidgebundenem Methionin in Weizen entstanden war.…”
Section: Die Späte Entdeckung Der Sulfoximingruppeunclassified
“…synthetisch hergestellt werden (Schema 1). [8] Die Sulfoximingruppe war bis dahin unbekannt gewesen. Natürlich war MSO (2) kein Naturstoff, da es chemisch aus peptidgebundenem Methionin in Weizen entstanden war.…”
unclassified
See 1 more Smart Citation
“…Research on the chemistry and properties of sulfoximines was triggered by the identification of methionine sulfoximine as the agent responsible for the toxicity of wheat flour treated with nitrogen trichloride (agene). , Nitrogen trichloride was used until the late 1940s for the bleaching of flour (agene process) when it was discovered that diets rich in agenized flour cause severe neurological disorders. Whitehead and Bentley accomplished the imidation of methionine sulfoxide with hydrazoic acid (HN 3 ) in the presence of concentrated sulfuric acid and demonstrated that the product is identical with the toxic factor isolated from agene-treated proteins . This was the first deliberate synthesis of a sulfoximine functionality and the interest in sulfoximine chemistry has increased steadily since then. Sulfoximines contain an amphoteric nitrogen and, with two nonidentical carbon substituents on the sulfur atom, a configurationally stable asymmetric sulfur moiety.…”
Section: Introductionmentioning
confidence: 99%
“…However, subsequent deprotection to produce the synthetically attractive free sulfoximines can be difficult and is often accompanied by a significant loss of material . The reaction of sulfoxides with HN 3 , as demonstrated in the seminal work of Whitehead and Bentley in 1951, provides free sulfoximines directly and is clearly more atom economic (HN 3 method) . This reaction is usually performed with sodium azide and sulfuric acid in CHCl 3 as solvent. ,, The method is exceedingly successful for the production of sulfoximines from sulfoxides if both carbon substituents are either methyl or aryl.…”
Section: Introductionmentioning
confidence: 99%